PENGARUH APLIKASI TOPIKAL DENGAN LARUTAN Na DAN SnF2 DALAM PENCEGAHAN KARIES GIGI - Ni Made Sirat (Jurnal Kesehatan Gigi (Dental Health Journal), 2014)
Dental and oral health has increased in the last century, but the prevalence of dental caries in children remains a clinical problem that significant. Suwelo reported prevalence of caries in preschool children in Jakarta 89.16 % with        def-t average of 7.02 or less 5.25 and the results of the survey in 10 provinces      (1984-1988 ) in urban areas, the prevalence of caries children aged 8 years 45.20 % with DMF-T 0.94 and according to the 1995 survey of DMF-T index 12 year olds showed an average 2.21 with a prevalence rate of 76.9 % . The purpose of this paper to examine the effectiveness of NaF and SnF2 solution in the prevention of dental caries. This study used a descriptive method. Missed issues through literature review by presenting theories of books, scientific magazines and Journal. The result of this research is a topical application with SnF2 solution 8% more effective than the solution NaF2% . Topical application with SnF2 solution 8% every year or 6 months can reduce a significant caries . SnF2 solution is a solution that is very active and having an activity of the solution is so high that when the fluoride solution in contact with emails regularly and will continue to make email more resistant to caries. High fluorine concentration and low pH can facilitate the formation of compounds fluorapatit. NaF2 % solution is not durable and should be stored in a dark bottle. Topical application with NaF is less effective because the patient must visit 4 times ( interval 1 week ) . End of reviewing fluorine , patients should rinse 1 times , so that the attachment of fluoride on teeth is not maximal . Topical fluoride application with SnF2 8 % more effective than the NaF in prevention of dental caries.